2008
DOI: 10.1017/s0266462308080495
|View full text |Cite
|
Sign up to set email alerts
|

Progression-free survival as a surrogate endpoint in advanced breast cancer

Abstract: Objectives Progression-free survival (PFS) has not been validated as a surrogate endpoint for overall survival (OS) for anthracycline (A) and taxane-based (T) chemotherapy in advanced breast cancer (ABC). Using trial-level, meta-analytic approaches, we evaluated PFS as a surrogate endpoint. Methods A literature review identified randomized, controlled A and T trials for ABC. Progression-based endpoints were classified by prospective definitions. Treatment effects were derived as hazard ratios for PFS (HRPFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 62 publications
(79 reference statements)
1
65
0
3
Order By: Relevance
“…Moreover, in a review of randomized control trials from 2004 to 2009 on breast, colorectal, and non-small cell lung cancer, Booth and Eisenhauer found a 26% increase in the use of PFS as a primary endpoint [19]. In contrast, breast cancer researchers showed that the prediction of OS based on PFS is uncertain [20,21]. Although we found an increased use of PFS as primary endpoint over time, this was not correlated with an increase in FDA approval rate.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a review of randomized control trials from 2004 to 2009 on breast, colorectal, and non-small cell lung cancer, Booth and Eisenhauer found a 26% increase in the use of PFS as a primary endpoint [19]. In contrast, breast cancer researchers showed that the prediction of OS based on PFS is uncertain [20,21]. Although we found an increased use of PFS as primary endpoint over time, this was not correlated with an increase in FDA approval rate.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] In nonvalidated cases such as breast cancer, PFS is considered an intermediate endpoint. [12,13] They are defined as the time between randomisation and local or distant recurrence for DFS, or the time between randomisation and progression, a second cancer or death by any cause for PFS. These endpoints have an undeniable clinical relevance because they measure the time during which there is no clinical evidence of tumour progression, thereby reflecting the anti-tumour action more directly than survival, and are not affected by later lines of treatment.…”
Section: Efficacy Endpointsmentioning
confidence: 99%
“…[8][9][10][11] Dans les cas non validés comme le cancer du sein, la PFS est considérée comme un critère intermédiaire. [12,13] La DFS est définie par le délai entre la randomisation et la récidive locale ou à distance. La PFS est définie par le délai entre la randomisation et la progression, un second cancer ou le décès quelle que soit la cause.…”
Section: Les Critères D'efficacitéunclassified